2021
DOI: 10.3390/metabo11020088
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Versatility of Mycobacterium tuberculosis during Infection and Dormancy

Abstract: Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis (TB), is a highly successful intracellular pathogen with the ability to withstand harsh conditions and reside long-term within its host. In the dormant and persistent states, the bacterium tunes its metabolism and is able to resist the actions of antibiotics. One of the main strategies Mtb adopts is through its metabolic versatility—it is able to cometabolize a variety of essential nutrients and direct these nutrients simultaneously to multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 178 publications
2
18
0
1
Order By: Relevance
“…When comparing 15 min vs. 12 h post-ALF exposure, some PIMs/LM/ManLAM biosynthesisassociated genes decreased their expression (pmmA, whiB2, pimF, pimA) while others increased (manB, pimB, embC) (Fig 2 and Table 2). This suggests a temporal and dynamic adaptation of M.tb's cell envelope components in response to ALF, in agreement with previous reports showing cell envelope remodeling of M.tb during infection and in response to different environmental conditions [33,34,[38][39][40][41][42][43]. pmmB expression was too low to be detected by our qPCR assay at either timepoints tested, thus no log2 fold changes are shown.…”
Section: Fig 2)supporting
confidence: 92%
“…When comparing 15 min vs. 12 h post-ALF exposure, some PIMs/LM/ManLAM biosynthesisassociated genes decreased their expression (pmmA, whiB2, pimF, pimA) while others increased (manB, pimB, embC) (Fig 2 and Table 2). This suggests a temporal and dynamic adaptation of M.tb's cell envelope components in response to ALF, in agreement with previous reports showing cell envelope remodeling of M.tb during infection and in response to different environmental conditions [33,34,[38][39][40][41][42][43]. pmmB expression was too low to be detected by our qPCR assay at either timepoints tested, thus no log2 fold changes are shown.…”
Section: Fig 2)supporting
confidence: 92%
“…Other PIMs/LM/ManLAM biosynthesis-associated genes slightly decreased (ppm1 and pimF), while others increased (manA and embC) (Table 2). Although most of the changes are not significant, the results suggest certain temporal and dynamic adaptation of M.tb's cell envelope components in response to ALF, in agreement with previous reports showing cell envelope remodeling of M.tb during infection and in response to different environmental conditions [26,27,[35][36][37][38][39][40]. pmmB expression was too low to be detected by our qPCR assay at either timepoints tested, thus no fold changes are shown.…”
Section: Figuresupporting
confidence: 91%
“…As a highly successful intracellular pathogen, M.tb can tolerate harsh conditions and reside long-term within its host by refining its metabolism. Studies conducted over the past 60 years have clearly shown that M.tb relies on fatty acids and cholesterol as important nutrients during infection ( Bloch and Segal, 1956 ; Chang and Guan, 2021 ). There are two types of growth behavior in bacteria: diauxic and coutilization of carbon sources.…”
Section: Diseases Related To Lipid Droplets and Immune Cellsmentioning
confidence: 99%